Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

X = y - 4-2x + 3y= 6Solve each system by equation

Sagot :

Answer: x=-6 and y=-2

Given:

[tex]\begin{gathered} x=y-4 \\ -2x+3y=6 \end{gathered}[/tex]

Having these two equations, we can substitute the first equation with the second equation to solve for y:

[tex]\begin{gathered} -2x+3y=6 \\ \end{gathered}[/tex]

Since the first equation says that x = y - 4,

[tex]\begin{gathered} -2x+3y=6 \\ -2(y-4)+3y=6 \\ -2y+8+3y=6 \\ -2y+3y=6-8 \\ y=-2 \end{gathered}[/tex]

Then, we will substitute this y-value to the first equation to solve for x.

[tex]\begin{gathered} x=y-4 \\ x=-2-4 \\ x=-6 \end{gathered}[/tex]

We now have the values x=-6 and y=-2. To check, let us substitute both values to the second equation

[tex]\begin{gathered} -2x+3y=6 \\ -2(-6)+3(-2)=6 \\ 12-6=6 \\ 6=6 \end{gathered}[/tex]

Therefore, the answer is correct, and the answer is x=-6 and y=-2

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.